“LIVING LIBRARY” AS AN INTERACTIVE EDUCATIONAL METHOD IN A UNIVERSITY UNDER MARTIAL LAW - Opryshko , Tetiana; Bulvinska , Oksana; Lytvynova , Anastasia (Continuing Professional Education: Theory and Practice, 2025)
The article is devoted to the presentation of the “Human Library” as an interactive educational method, as well as to the experience of its implementation in the educational process of Borys Grinchenko Kyiv Metropolitan University. It emphasizes that under martial law, ethical and tactful communication with military personnel, often traumatized by combat experience, is crucial for Ukrainian society as a whole, particularly for participants in the educational process in higher education institutions. It is highlighted that the “Human Library” method, designed to overcome differences between people through live interaction and to combat prejudice and stereotypes, can contribute to this goal. The essence of the interactive “Human Library” method is revealed, in which the role of books is performed by living people who share their personal stories. It is stressed that the application of this method in higher education contributes to solving a range of tasks: educational, motivational, formative, communicative, and developmental. The article presents the experience of the Library of Borys Grinchenko Kyiv Metropolitan University, which traditionally organizes “Human Library” events by inviting military personnel to serve as “living books” and engaging participants of the educational process from the Faculty of Journalism and other faculties. Based on the results of these events, students complete practical assignments by preparing media products of a defined genre – such as a profile essay, a photo report, or a video/audio recording of the event – thereby improving their professional skills. The “Human Library” method has significant potential for enhancing the quality of professional education and for developing students’ professional competencies, particularly in the field of Journalism.